Study on Adaptive PID Control Algorithm Based on RBF Neural Network - Xuemei Qi; Jingdong Zhang (Institute of Advanced Engineering and Science, 2015)
Aim at the limitation of traditional PID controller has certain limitation, the traditional PID control is often difficult to obtain satisfactory control performance, and the RBF neural network is difficult to meet the requirement of real-time control system. To overcome it, an adaptive PID control strategy based on (RBF) neural network is proposed in this paper. The results show that the proposed controller is practical and effective, because of the adaptability, strong robustness and satisfactory control performance. It is also revealed from simulation results that the proposed control algorithm is valid for DC motor and also provides the theoretical and experimental basis. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.6958